A 19-Billion Blind Spot: State Pension Spending. (April 2020) - Costrell, Robert M.; Hitt, Collin; Shuls, James V.
In this brief, we examine an important but obscure form of state spending on K–12 education—state subsidies of school district pension costs. In 2018, this exceeded 19 billion across 23 states. To put that amount into perspective, 2018 federal spending on Title I programs was 15.8 billion. This revenue stream is often ignored in analyses of state aid for K–12 and its distribution across districts. Until recently, accounting standards did not require pension plans to report these implicit subsidies to the school districts, so they did not typically know the size of their subsidy. In some important cases, it was missing from state totals for education aid. In the first comprehensive tabulation of these data, we show that this subsidy can be as much as 2, 400 per pupil, as it is in Connecticut. In Illinois, it comprises an additional 56% of state spending on K–12 on top of all formula and categorical aid.